Language choices between partners in bilingual relationships - Stępkowska, Agnieszka (Penerbit Universiti Kebangsaan Malaysia, 2021)
The paper focuses on the language choices among a sample of bilingual heterosexual couples in the less studied Polish context. Drawing on 24 in-depth interviews I examine the reasons for language choices in the couple, with the most engaging arguments being when the minority language is chosen. In the results section, I give the voice to the couples by inserting extracts from the interviews, illustrating the dyadic communication between the partners. The analysis is grounded in the sociolinguistic perspective bringing together linguistic and cultural aspects. Through these themes, I come to a more detailed account of communication scenarios conditioned by the L2 command of either of the partners. I report on the couples’ language repertoires and the languages of their first contact that result from the individual trajectories of their L2 acquisition and impinge on the agreed language choices. My data suggest that bilingual couples do not, as it might otherwise be expected, always end up using the language of the surrounding society. The findings reveal a relative stability of linguistic choices, but also some deviations from once adopted communication patterns. The paper shows that language choice and proficiency are closely connected, but also that other factors come into play.